Physiological, biochemical and psychological markers of strenuous training-induced fatigue - Rietjens, G. J. W. M.; Kuipers, H.; Adam, J. J.; Saris, W. H. M.; van Breda, E.; van Hamont, D.; Keizer, H. A. (International Journal of Sports Medicine, 2005)
The purpose of the study was to investigate whether severe fatigue, possibly leading to overreaching, could be diagnosed at an early stage by a combination of parameters. Seven well-trained male subjects (age [mean ± SD]: 25.3 ± 4.7 yr; body mass: 76± 6.6 kg; VO2max: 61.1 ± 7 ml · kg-1 · min-1) increased their training load by doubling their training volume and increasing the intensity by 15 % over a period of two weeks. Before and after this intensified training period subjects underwent a series of tests including a maximal incremental cycle ergometer test (Wmax) with continuous ventilatory measurements and blood lactate values, time trial, basal blood parameter tests (red and white blood profile), hormones [growth hormone (GH), insulin-like growth factor 1(IGF-1), adreno-corticotropic hormone (ACTH), cortisol], neuro-endocrine stress test [short insulin tolerance test (SITT), combined anterior pituitary test (CAPT) and exercise], a shortened Profile of Mood State (POMS), the estimated rate of perceived exertion (RPE) and a cognitive reaction time test. The intensified training period resulted in a significant increase of the training load (p < 0.01), training monotony (p < 0.01) and training strain (p < 0.01). The RPE during training increased significantly (p < 0.01) during the intensified training period. Total mood score obtained from the POMS tended to increase (p = 0.06), reflecting an increase in worse mood state. A novel finding was that reaction times increased significantly, indicating that overreaching might adversely affect speed of information processing by the brain, especially for the most difficult conditions. After the intensified training period, neither changes in exercise-induced plasma hormone values, nor SITT values were observed. During the CAPT only cortisol showed a significant decrease after the intensified training period. Hemoglobin showed a significant decrease after the intensified training period whereas hematocrit, red blood cell count (RBC) and MCV tended to decrease. The intensified training had no effect on physical performance (Wmax or time trial), maximal blood lactate, maximal heart rate and white blood cell profile. The most sensitive parameters for detecting overreaching are reaction time performance (indicative for cognitive brain functioning), RPE and to a lesser extend the shortened POMS. This strongly suggests, that central fatigue precedes peripheral fatigue. All other systems,including the neuro-endocrine, are more robust and react most likely at a later stage in exhaustive training periods.